2011
DOI: 10.1007/s11274-011-0845-9
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic characteristics of plant-esterase from wheat flour

Abstract: A plant-esterase extracted from wheat flour and purified with a PEG1000/NaH(2)PO(4) aqueous two-phase system was characterized for its catalytic characteristics. The optimal condition for plant-esterase to catalyze 1-naphthyl acetate was at 30°C, pH 6.5. It kept stability at 20°C during 120 min and at pH 5.5 during 60 h. The effects of metal ions, chemical modification reagents and pesticides on plant-esterase activity were investigated. It was found that Ba(2+) and Pb(2+) at concentrations of 20 mM significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…In particular, only 9.3 ± 1.9% of the EST2 activity was inhibited by 30 µM NBS (Supplementary Figure S1), corresponding to the final amount of oxidant in the inhibition assay of NBS-oxidized pesticides. These results are in agreement with data obtained with other esterase activities [31]. To avoid deviancy in results, all the measurements were carried out using a reference enzymatic activity of EST2 in both normal and oxidative (with addition of NBS) conditions.…”
Section: Effects Of Nbs On Est2 Activitysupporting
confidence: 88%
“…In particular, only 9.3 ± 1.9% of the EST2 activity was inhibited by 30 µM NBS (Supplementary Figure S1), corresponding to the final amount of oxidant in the inhibition assay of NBS-oxidized pesticides. These results are in agreement with data obtained with other esterase activities [31]. To avoid deviancy in results, all the measurements were carried out using a reference enzymatic activity of EST2 in both normal and oxidative (with addition of NBS) conditions.…”
Section: Effects Of Nbs On Est2 Activitysupporting
confidence: 88%
“…Moreover, EDTA positively affected esterase activity, indicating that divalent cations inhibit J. curcas DLH, as supported by our other assays with different ions. Similar effects were also observed for other plant esterases/lipases such as C. pepo [39], Glycine max, Oryza sativa [42], and those in wheat flour [43]. Metal ions can affect esterases/lipases and other α/β hydrolases activity by different mechanisms such as by coordinating with active site residues [44], overall structure alteration by allosteric regulation [44,45], surface potential alteration (a pH-dependent event) [46], and reaction equilibrium dislocation through low-soluble salt production with one of the hydrolysis reaction products, namely the carboxylic acid (mainly described for Ca 2+ [47]).…”
Section: Discussionsupporting
confidence: 76%
“…The LODs obtained for methamidophos and phoxim with purified esterase were lower than the maximum residue limits (MRLs) for these OPs in food. According to Hou et al, 142 the catalytic characteristics of a plant esterase extracted from wheat flour and purified with a PEG1000/NaH 2 PO 4 aqueous two-phase system were reported. The results showed that the chemical modification significantly influenced the activity of plant esterase.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%